Suppressing STAT3 activity protects the endothelial barrier from VEGF-mediated vascular permeability - Li Wang; Matteo Astone; Sk. Kayum Alam; Zhu Zhu; Wuhong Pei; David A. Frank; Shawn M. Burgess; Luke H. Hoeppner (The Company of Biologists, 2021)
Vascular permeability triggered by inflammation or ischemia promotes edema, exacerbates disease progression and impairs tissue recovery. Vascular endothelial growth factor (VEGF) is a potent inducer of vascular permeability. VEGF plays an integral role in regulating vascular barrier function physiologically and in pathologies, including cancer, stroke, cardiovascular disease, retinal conditions and COVID-19-associated pulmonary edema, sepsis and acute lung injury. Understanding temporal molecular regulation of VEGF-induced vascular permeability will facilitate developing therapeutics to inhibit vascular permeability, while preserving tissue-restorative angiogenesis. Here, we demonstrate that VEGF signals through signal transducer and activator of transcription 3 (STAT3) to promote vascular permeability. We show that genetic STAT3 ablation reduces vascular permeability in STAT3-deficient endothelium of mice and VEGF-inducible zebrafish crossed with CRISPR/Cas9-generated Stat3 knockout zebrafish. Intercellular adhesion molecule 1 (ICAM-1) expression is transcriptionally regulated by STAT3, and VEGF-dependent STAT3 activation is regulated by JAK2. Pyrimethamine, an FDA-approved antimicrobial agent that inhibits STAT3-dependent transcription, substantially reduces VEGF-induced vascular permeability in zebrafish, mouse and human endothelium. Collectively, our findings suggest that VEGF/VEGFR-2/JAK2/STAT3 signaling regulates vascular barrier integrity, and inhibition of STAT3-dependent activity reduces VEGF-induced vascular permeability. This article has an associated First Person interview with the first author of the paper.